The organization of medical actions at wounds of finitenesses, the characteristic of possible complications and outcomes - A. M. Amirov (Юг России: экология, развитие, 2015)
The questions of rendering of the surgical help by the wounded man in finiteness at various stages of medical evacuation are considered. Outcomes of development of is purulent-septic complications at military men with fighting traumas of finitenesses depending on character and localization of the received wounds are studied. Dependence of outcomes of treatment on terms medical evacuation and duly rendering of the specialized surgical help is revealed.